2018
DOI: 10.1002/clc.23126
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tricuspid regurgitation and right ventricular dysfunction on outcomes after transcatheter aortic valve replacement: A systematic review and meta‐analysis

Abstract: Far less attention has been paid to the prognostic effect of right‐side heart disease on outcomes after transcatheter aortic valve replacement (TAVR) when compared with the left side. Therefore, we performed a systematic review and meta‐analysis on the impact of tricuspid regurgitation (TR) and right ventricular (RV) dysfunction on outcomes after TAVR. We hypothesized that TR and RV dysfunction may have a deleterious effect on outcomes after TAVR. Article revealing the prognostic effect of TR and RV dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
2
16
0
3
Order By: Relevance
“…Prevalence and prognosis significance of RV dysfunction in patients undergoing TAVI have been a matter of debate in the last years. Regarding prognosis, two recent meta‐analysis addressing this issue show similar results and it is well accepted now that the presence of RV dysfunction carries a higher mortality risk after TAVI 15,16 . Moreover, a recent study of more than 1000 patients, not included in the mentioned meta‐analysis, confirms that RV dysfunction at baseline was associated with a more than twofold increased risk of cardiovascular death at 1 year after TAVI, with a gradient of risk according to RV recovery, being strongest independent predictor of 1‐year cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 56%
“…Prevalence and prognosis significance of RV dysfunction in patients undergoing TAVI have been a matter of debate in the last years. Regarding prognosis, two recent meta‐analysis addressing this issue show similar results and it is well accepted now that the presence of RV dysfunction carries a higher mortality risk after TAVI 15,16 . Moreover, a recent study of more than 1000 patients, not included in the mentioned meta‐analysis, confirms that RV dysfunction at baseline was associated with a more than twofold increased risk of cardiovascular death at 1 year after TAVI, with a gradient of risk according to RV recovery, being strongest independent predictor of 1‐year cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 56%
“…Two studies in our analysis reported higher rates of moderate to severe TR in ViV TAVR group. It has been previously shown that moderate to severe tricuspid regurgitation, right ventricular dysfunction and pulmonary hypertension are predictors of poor prognosis in patients undergoing native valve TAVR though their influence on ViV TAVR is yet to be established 22 . Yet, despite this greater predicted risk, the 30‐day mortality in ViV TAVR group was lower suggesting that ViV TAVR is a safe alternative for these patients at high operative risk.…”
Section: Discussionmentioning
confidence: 96%
“…In a more “global” view of the heart, its functional capacity equally depends on the right heart function, and the association of echocardiographic measures on RV contractility with patient outcomes has not been widely investigated. Fan et al found in a meta‐analysis with more than 6,400 patients preexisting RV dysfunction and concomitant moderate to severe tricuspid regurgitation as a predictor for adverse outcomes after TAVR 22 . On the other hand, Cremer et al showed relevant worsening in RV function 30 days after AVR in patients with dilated RV at baseline, mild TR, and postsurgical treatment 23 .…”
Section: Discussionmentioning
confidence: 99%